Professores de canto e fonoaudiólogos: conhecimento interdisciplinar na atuação com cantores - Colepicolo, Carla Rosati (2018)
Introduction: The development of voice research has shown common interests in some areas of knowledge. Singing teachers and speech therapists have approached their knowledges and a joint work can provide a growth for all professionals involved with the singing voice. Objective: to analyze the joint performance of singing teachers and speech therapists in working with singers. Method: intentional sample with five singing teachers and five recognized speech therapists working with the voice of singers. These answered five semi-directed questions that were audio-taped and transcribed. The material was analyzed and categorized. Results: according to the audiologists interviewed, it is up to them to understand the context of the singer; diagnose and carry out actions of prevention and rehabilitation of the voice; work with the physiology and vocal structure. The singing teachers said that the role of speech therapist is to work with health and voice alteration. The vocal orientation was pointed out by the two groups of professionals. According to the singing teachers, their role is to detect the vocal alteration and refer to the other specialist. For speech therapists, only the singing teacher should do the vocal classification and tuning. Expressiveness, musicality, technique, choice of repertoire, style and vocal aesthetics were items indicated by both professionals to explain the role of the singing teacher. The role of adjusting the vocal structure in order to meet the demand was a response considered as the role of speech therapists and singing teachers. The performance among professionals is understood and can happen: independently or complementary and associated or still, with interaction, communication and continuity in the work with singers. Some aspects were mentioned that intercept the relations between these specialists in the performance with related singers: to the vocal well-being; to the context lived by the singers; the roles of professionals; the terminology used; the relevance of the specialty in the singing voice and the counterpoint between science versus art. Conclusion: singing teachers and speech therapists establish different and unique working relationships with singers, characterized by contact, exchanges of knowledge, referrals, support, recognition, joint action and interdisciplinary action. Both vocal teachers and speech therapists say they need to work together because they understand that the other professional can develop the vocal aspect or adjust the vocal apparatus of the singers identified in their evaluation with more precision, more effectiveness or more specificity